Ethnographic Study of Pre-exposure Prophylaxis in HIV/AIDS Prevention and Control in Makassar, South Sulawesi Province - Muh. Arsyad Rahman; Shanti Riskiyani (Universitas Hamzanwadi, 2024)
The study aimed to explore information about factors and social realities that influence pre-exposure prophylaxis (PrEP) seeking and accessing behavior in Makassar, South Sulawesi Province. This basic research uses a type of ethnographic research, data from the views of the community (emic views), namely health workers, program managers, PrEP service recipients, key groups, related community groups, and communities. Results show that people with high HIV potential are generally unwilling or embarrassed to disclose and often fill out paperwork dishonestly, due to cultural realities. Customs, habits, and practices among potential PrEP clients, known as user culture, make it difficult for interventions to select appropriate and accurate health services, thus affecting future transmission maps. In conclusion, potential users are still secretive, and their sexual activities and places of use of PrEP services do not want to be known by others. The social and cultural reality demonstrated by PrEP users at the Andalas Puskesmas is that some persons tend to avoid the Andalas Puskesmas working area, claiming that they are embarrassed to be seen by residents.